Asuhan Keperawatan Pada Tn. M Dengan PPOK Di Ruang Pejuang RSUD Bangkinang Tahun 2024 - Diki Saputra; Riani Riani (LPPI Yayasan Almahmudi Bin Dahlan, 2025)
Chronic Obstructive Pulmonary Disease or often abbreviated as COPD is a term used for a number of diseases that attack the lungs for the long term. This disease blocks the flow of air from the lungs so that sufferers will have difficulty breathing. The purpose of this study was to examine and implement nursing care for patients with COPD in the Pejuang room of Bangkinang Hospital in 2024. This research method uses a descriptive research design in the form of a case study. The subject in the case report is Mr. M who is 47 years old with COPD in the Pejuang room of Bangkinang Hospital which was carried out for 3 days on June 26 to 28, 2024. Data obtained through interviews, physical examinations and supporting examinations. During the assessment, the client felt shortness of breath, felt weak, and had decreased appetite. Therefore, the researcher established 3 (three) main problems with the nursing diagnosis of ineffective airway clearance related to airway spasm, ineffective breathing pattern related to respiratory effort obstruction, activity intolerance related to imbalance between oxygen supply and demand. Three-day nursing evaluation of the client, namely the problem resolved. The report of the results of this case study is expected to be a guideline for researchers in providing nursing care to patients with COPD, as a reference in learning on campus, and as a reference in providing nursing care to patients by nurses in hospitals.